ANALYSIS OF INFORMATION ABOUT THE FERGHANA REGION IN DOCUMENTS OF THE COURT OF THE GENERAL GOVERNORATE OF TURKESTAN - Kenjayev Nurolim Jumanazarovich (Scholars Digest Publishing, 2023)
The Kokan Khanate, one of the last territories occupied by tsarism in Turkestan, was abolished as a state in February 1876. In its place, the Fergana region was created. Information about these actions is given in order No. 244 of the first Turkestan Governor-General K.P. Kaufman dated October 30, 1876. Information on the administration of the Fergana region was collected.